Various Uses of Laryngeal Mask Airway during Tracheal Surgery - Celik, Ali; Sayan, Muhammet; Kankoc, Aykut; Tombul, Ismail; Kurul, Ismail Cüneyt; Tastepe, Abdullah Irfan (The Thoracic and Cardiovascular Surgeon, 2021)
Background The use of laryngeal mask airway (LMA) ventilation in surgeries to be performed in upper tracheal stenosis has been reported in the case series. However, there is no generally accepted standardized approach for the use of LMA. In this study, LMA usage areas and advantages of trachea surgery were examined.Methods The records of 21 patients who underwent tracheal surgery using LMA ventilation between March 2016 and May 2020 were evaluated retrospectively. The patient data were analyzed according to age, gender, mean follow-up time, surgical indication, mean tracheal resection length, anastomosis duration, mean oxygen saturation, mean end-tidal CO2 levels, and postoperative complications.Results Four patients were female and 17 were male, their median age was 43 (11–72 range) and the mean follow-up time was 17.6 months. The most common surgical indication was postintubation tracheal stenosis. The mean tracheal resection length was 26.6 mm and the mean anastomosis duration was 11.3 minutes. The mean pulse oximetry and mean end-tidal CO2 during laryngeal mask ventilation was 97.6% ± 2.1 and 38.1 ± 2.8 mm Hg, respectively. Postoperative complications were higher in patients with comorbidities.Conclusion LMA-assisted tracheal surgery is a method that can be used safely as a standard technique in the surgery of benign and malignant diseases of both the upper and lower airway performed on pediatric patients, patients with tracheostomy, and suitable patients with tracheoesophageal fistula.
Keywords: trachea; surgical indication; surgery; complications; anesthesia